2021
DOI: 10.1021/acsanm.1c02992
|View full text |Cite
|
Sign up to set email alerts
|

YVO4 Nanoparticles Doped with Eu3+ and Nd3+ for Optical Nanothermometry

Abstract: The ongoing research in biology, medicine, and technology requires accurate measurement and control of temperature at micro and nanoscales. Rare-earth-doped luminescence nanoparticles were found to be one of the most perspective systems for noncontact ratiometric temperature sensing for various applications. Despite plenty of single-doped sensors with thermally coupled levels, the development of a dual-center thermometer with enhanced thermometric performances is still challenging. Here, we demonstrate two app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…At the same time, the almost constant decay time of Eu 3þ implies that a pronounced To provide a more detailed analysis, the radiative and nonradiative decay rates at various temperatures were calculated using 4f-4f intensity theory. [57][58][59][60][61][62][63][64][65] The total radiative decay rate (A R ) is estimated by taking the sum of radiative rates A 0J for each 5 D 0 -7 F J transition given by…”
Section: The Phenomenon Of Diverse Thermal Quenchingmentioning
confidence: 99%
“…At the same time, the almost constant decay time of Eu 3þ implies that a pronounced To provide a more detailed analysis, the radiative and nonradiative decay rates at various temperatures were calculated using 4f-4f intensity theory. [57][58][59][60][61][62][63][64][65] The total radiative decay rate (A R ) is estimated by taking the sum of radiative rates A 0J for each 5 D 0 -7 F J transition given by…”
Section: The Phenomenon Of Diverse Thermal Quenchingmentioning
confidence: 99%
“…The increase of the Yb 3+ doping concentration resulted in the significant enhancement of Yb 3+ luminescence band intensity (>850 nm) for mixed samples, while Yb 3+ emission almost did not change for codoped samples. Noteworthily, contrary to YVO 4 :Eu 3+ /Nd 3+ nanothermometers, mixed thermal sensors display much worse thermal performances compared to codoped ones. , In addition to relative sensitivity, we calculated absolute thermal sensitivity, S a , which displayed an absolute LIR change with temperature variation ( S a = dLIR/d T ). Figure S6 presents the temperature evolution of S a of codoped and mixed LuVO 4 :Nd 3+ /Yb 3+ phosphors.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared with the conventional contacted thermometers, a lot of attention has been attracted by luminescence thermometers, which utilize temperature-associated fluorescence characteristics, such as fluorescence intensity ratio (FIR), band position, decay time, full width at half-maximum of emission band, etc., of luminescent materials because of their advantages of rapid response, high accuracy/resolution, and contactless characteristic. , Particularly, by adopting the FIR technique, optical thermometry is extensively adopted, in which the temperature-related emission intensities of thermally coupled levels (TCLs) of rare-earth ions are investigated. , Fu et al revealed that the thermometric properties of rare-earth ions, which were based on their TCLs, can be adjusted by controlling the excitation wavelength and utilizing tridoping engineering. , However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity ( S r ) triggered by the small energy band gap of TCLs (200 ≤ Δ E ≤ 2000 cm –1 ). , For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ /Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ /Eu 3+ , with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing. Thereby, the utilization of the temperature-dependent FIR value of non-TCLs is a facile strategy to manipulate the thermometric behaviors of luminescent materials.…”
Section: Introductionmentioning
confidence: 99%